Willa the silver glitter dragon - Mara, Maddy (2021)
"Willa and her friends have a powerful magic inside of them-they each have the ability to transform into a Glitter Dragon Girl ... The troublesome Shadow Sprites are after the Tree Queen's magic again, and it can only be saved by a special potion. The Dragon Girls must work together to gather all of the ingredients. Willa is leading their quest, but she's scared of what might happen if they don't succeed"--
Reading Level: Grade 3.
Appeals to: 2nd-3rd Graders.
Keywords: Dragons -- Juvenile fiction; Magic -- Juvenile fiction; Friendship -- Juvenile fiction; Girls -- Juvenile fiction; Quests (Expeditions) -- Juvenile fiction; Dragons -- Fiction; Magic -- Fiction; Friendship -- Fiction; Dragons -- Romans, nouvelles, etc. pour la jeunesse; Amitié -- Romans, nouvelles, etc. pour la jeunesse; Dragons; Friendship; Magic; Friendships -- Juvenile fiction; Children's stories; Fantasy -- Juvenile fiction; Fantasy fiction; Fiction; Juvenile works; Fantasy fiction; Fantasy fiction